Exploring Cr/CrNx/CryCz/Cr-DLC film for geophysical prospecting. (May 2014) - Zhang, Q. S.; Deng, M.; Ai, J.; Zhang, L.; Huang, J. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Cr(chromium)/CrNx/CryCz/Cr-DLC (diamond-like carbon) film in a mid-frequency dual magnetron sputtering was explored for its application in geophysical prospecting. The influences of pulsed substrate bias voltage on the surface morphology, microstructure, hardness, adhesion and friction property of the film were investigated. The proposed film provides a coating solution for executive components of geophysical instruments. Cr-DLC film at −140 V exhibited good combined properties: high hardness up to 32·5 GPa; good adhesion [Lc (critical loads) up to 63·7 N]; superior wear resistance and friction coefficient low to 0·126 at ambient atmosphere and 0·052 in a seawater environment.